Gerakan Sosial Keagamaan Pendidikan Islam Masa Kolonialisme - Mujianto Solichin; M. Ansor Anwar (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2020)
Historically, Ulema play an important role in religious-social movement and Islamic education. They have well established social and intellectual basis in maintaining their key position to spread Islam in Indonesia. During Islamic Monarchy throughout pre-colonialism in archipelago, their key positions have been described an elite religious leader and being a part of the ruler at that period. At the beginning, the Dutch as the colonialist, did not interfere on Islamic education system. However, step by step they interfered by giving pressure and confronting on the monarchy power, especially religious social institution. During colonialism period, the growth of religious social institution, therefore has led to the establishing of religious authority. Furthermore, this become institutional basis for the ulema to spread Islam. Moreover, they also have important contributions in religious practice, build up religious social movement, including Islamic education in their regions. During 17 till 19 century, as mecca became the religious spirit in east Hindia, their networking with ulema from Middle East intensively spread the intellectual kernel as well as building Islamic transmission. They use their intellectual to spread the Islam across archipelago.